Menjembatani Pemikiran: Tinjauan Pustaka Sistematis tentang Pendekatan STEM dalam Menumbuhkan Berpikir Kritis pada Pendidikan Sains - Bintan Nuril Irvaniyah; Parno; Marlina Ali (Jurnal Penelitian Pendidikan IPA, 2025)
This study systematically reviews STEM-based learning models and media designed to enhance students’ critical thinking skills. A total of 27 Scopus-indexed articles published between 2020 and 2024 were analyzed using a systematic literature review (SLR) approach. The analysis focused on publication trends, thematic emphases, key findings, and implementation challenges. Results indicate that STEM integration through models such as Problem-Based Learning (PBL) and Inquiry-based learning supports the development of several critical thinking indicators, especially explanation, inference, and decision-making. Quantitative findings from some studies show that improvements are often moderate, with the indicator of advance clarification consistently emerging as the weakest. Media such as worksheets and e-modules are found to facilitate structured inquiry and independent learning, yet their effectiveness remains constrained by limited teacher readiness, short implementation cycles, and challenges in interdisciplinary integration. STEM-based learning contributes positively to critical thinking development, though its impact varies across indicators and contexts. Future studies are recommended to design and evaluate targeted learning models, such as the Clarity Learning Model (CLM), which focuses on strengthening advance clarification while supporting other critical thinking dimensions.